An investigation of the faecal microbiome of diarrhoeic and non diarrhoeic kittens : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Manawatū, New Zealand - Owen, Rebecca (Massey University, 2025)
Kittens change from birth to adulthood in different ways, some of these are anatomical, physiological, cognitive, behavioural, as well as nutritional, and microbial. The microbial adaptations in relation to changes in diet and faecal consistency during the weaning period are the main focus of this study. During the weaning period, it is relatively common for kittens to develop diarrhoea. Unfortunately, diarrhoea in this vulnerable population, particularly before 8 weeks of age, can lead to death due to the secondary dehydration, hypothermia and hypoglycaemia. There are many different causes of diarrhoea, both infectious and non-infectious. In many cases, infectious cases of diarrhoea are ruled out through appropriate testing. This leaves a population of kittens with an unexplained, non-infectious diarrhoea. In recent years, it has increasingly been suggested that small changes in a previously stable microbiome can impact the health and faecal consistency of an individual, causing disorders such as inflammatory bowel disease (IBD). The intestinal microbiome refers to the bacterial communities found within the gastrointestinal tract. When an imbalance in the microbiome predisposes or causes disease, this is referred to as a dysbiosis. The aim of this study was to investigate the microbiome of diarrhoeic and non-diarrhoeic kittens, during and after the weaning period. It was hypothesised that kittens that developed diarrhoea, had a different microbiome to kittens that did not. Samples from 16 litters (13 diarrhoeic litters and 3 non diarrhoeic litters) underwent 16S rRNA PCR and sequencing to determine the bacterial communities found within the faecal microbiome. Observations from this study found differences between diarrhoeic and non-diarrhoeic litters, particularly between the pre-weaning, pre-diarrhoea and post-diarrhoea weaned, recovered samples. The pre-weaning, pre-diarrhoea samples had the lowest (but non-significant) Shannon diversity of all samples, indicating the possibility of a dysbiosis preceding diarrhoea. This study also identified differences between the during-weaning and post-weaning microbiome. The two diet groups in this study, although similar, had a significantly different Jaccard distance. The microbiomes of queens and kittens were also significantly different, irrespective of diarrhoeic status, diet, and owner. This study helps to fill the gap in knowledge and provides some new information about diarrhoeic and non-diarrhoeic kittens during and after the weaning period and identifies a potential dysbiosis that precedes non-infectious diarrhoea. Once this information is established with a bigger study, prevention or treatment methods can be investigated for kittens who are identified to be at risk of diarrhoea or develop non-infectious diarrhoea. This information would be of benefit to veterinarians, cat breeders and animal shelters, with the hope that these at-risk kittens could be better managed or even possibly prevent one of the most common problems kittens face in their early life.
Figure 1.1 is reused under a Creative Commons Attribution-NonCommercial-NoDerivs 3.0 Unported license. Figure 1.4 (= Fukuda et al., 2018 Fig 1) was removed for copyright reasons.
Keywords: 300903 Veterinary bacteriology